2022
DOI: 10.1111/cbdd.14129
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of recent advances in the biological activities of quinazolines

Abstract: Quinazoline heterocycles are critical in the development of medications.Quinazoline derivatives have been intensively researched, providing a wide range of compounds with diverse biological roles. The quinazoline nucleus has garnered a lot of attention in medical chemistry in recent years. It was assumed to be a pharmacophore component in the development of physiologically interesting drugs. This review is an attempt to increase the potential of quinazoline by highlighting a wide range of advancements demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…These heterocycles are essential constituents of natural systems and are frequently found in alkaloids and many bioactive molecules [10] . The unique structure of quinazolines with two fused six‐membered aromatic rings, benzene, and a pyrimidine ring, impart to it interesting properties that can be exploited in biological systems [11–14] . The presence of the benzene ring enhances the reactivity of the 3,4‐double bond, making quinazolines very reactive to incoming nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These heterocycles are essential constituents of natural systems and are frequently found in alkaloids and many bioactive molecules [10] . The unique structure of quinazolines with two fused six‐membered aromatic rings, benzene, and a pyrimidine ring, impart to it interesting properties that can be exploited in biological systems [11–14] . The presence of the benzene ring enhances the reactivity of the 3,4‐double bond, making quinazolines very reactive to incoming nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The unique structure of quinazolines with two fused six-membered aromatic rings, benzene, and a pyrimidine ring, impart to it interesting properties that can be exploited in biological systems. [11][12][13][14] The presence of the benzene ring enhances the reactivity of the 3,4-double bond, making quinazolines very reactive to incoming nucleophiles. They have a wide range of versatile applications that include a plethora of biological activities like anti-cancer, anti-inflammatory, antiviral, antibiotics, and many other medicinal applications.…”
Section: Introductionmentioning
confidence: 99%
“…The commercially available 2,4-dichloro-6,7-dimethoxyquinazoline ( 7 ) was chosen for this purpose ( Scheme 3 ). The common dimethoxy motif is also found in a variety of quinazoline-based pharmaceuticals [ 2 3 8 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quinazoline core is a privileged structure with a wide range of applications. Quinazoline derivatives exhibit a broad spectrum of biological activities, finding use as anticancer, antimicrobial, antimalarial, and antiviral agents [1,2]. Furthermore, numerous 2-amino-6,7-dimethoxyquinazoline analogs are extensively employed as α 1 -adrenoceptor blockers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Quinazoline heterocycles are an important group of nitrogen-containing cyclic compounds. These heterocycles are vital in the development of pharmaceuticals and provide a variety of biologically active scaffolds [97][98] . It has been reported that quinazoline derivatives have various biological and therapeutic properties including antibacterial, anti-in ammatory, antifungul, anticancer, anti-plasmodial, anti-tumor, antimicrobial and antioxidant ability [99][100][101] .…”
Section: Introductionmentioning
confidence: 99%